Evolving digital leadership : how to be a digital leader in tomorrow's disruptive world - Brett, James (Findaway World : Gildan Audio, 2020)
Get ready to be an effective digital leader, influencer, disruptor, and catalyst for change in the digital world!As a leader you need to constantly evolve to achieve sustained success. The world is being transformed by Digital. The pace of change is constantly accelerating and volatility and complexity are the new norms. Digital leaders are at the forefront of these waves of change, creating new markets and transforming traditional ones. This audio book is a framework and set of tools that will help you develop a deep awareness of yourself, your teams, and your stakeholders. The powerful four-step process (designed to remain relevant over time) ensures that you are embracing adversity, driving disruption, and unlocking your full leadership potential. You'll Learn: how to be an influencer, disrupter, and catalyst for change in a disruptive world; five key career recommendations from 40 digital leaders with more than 400 years of combined experience; how to use the four steps of the Unnatural Selection framework to facilitate your personal evolution and digital leadership success; how to demystify what makes people tick using the Human Full Stack, which is a model analogous to the technical full stack, so that complex behaviors are easier to understand; and more.